Incidence, Options of Medical Intervention and Post-Intervention Follow-up of Patients with Patent Ductus Arteriosus: An Experience in Combined Military Hospital, Dhaka - Maksud, Aziz Al; Begum, Nurun Nahar Fatema; Sarker, Md Ferdousur Rahman (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Patent Ductus Arteriosus (PDA) is the fifth most common congenital cardiac defect. A large number of neonates with PDA get admitted to hospital each year. If it remains undetected in the neonatal period, patient may develop several consequences in later life which are very difficult to manage. Objectives: To determine the incidence of PDA in newborn and it’s outcome following different modalities of medical intervention. Methods: This cross-sectional observational follow-up study carried out in Combined Military Hospital (CMH), Dhaka from January 2016 to December 2017. Total 50 cases of isolated PDA were included in this study. Results: Out of 50 cases, 80% were preterm and 20% were term. Most of the PDA (35) were of moderate size. Total 11 patients had spontaneous closure and 21 patients had closure after Indomethacin therapy. Among 8 patients who did not respond to Indomethacin, 1 died during the therapy and 7 patients underwent successful trans-catheter coil occlusion where 1 patient required second coil implantation. Remaining 10 patients were selected for trans-catheter device closure and complete closure was observed in 100% of these cases within 3 months of device deployment. Conclusion: Early diagnosis, appropriate pharmacological and medical interventional management can cure nearly all the cases of PDA, avoiding surgery which is also a gold standard safe and effective alternative treatment of PDA. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 61-65